The Outcome of Pediatric Femur Fractures Fixation with Titanium Elas-tic Nail System - Acharya, Devendra; Neupane, Gaurav; Shrestha, Sujit Raj; Bhandari, Pratap Babu; KC, Saugat (Nepal Orthopaedic Association Journal, 2023)
Introduction: Pediatric femur fractures are commonly present because of high-velocity injuries in children. It is the most common reason for pediatric hospital admission due to trauma. There is a spectrum of choices for fixation for these fractures, but the best method has always been debated. In this study, we share our experience of fixation of pediatric diaphyseal femur fractures at our center using Titanium Elastic Nail System.Method: A hospital-based prospective study was conducted between January 2019 to June 2022. Patients aged between 5 to 12 years with shaft of femur fracture and body weight of less than 49 kg were included in the study. Children with pathological fractures, ipsilateral limb injuries, metabolic bone disease, and neuromuscular disorders were excluded. All patients were followed up till nine months with radiographic and clinical assessment.Result: A total of 47 children were included in this study. The mean age was 8.08±2.17 years, and the mean weight was 26.55±6.46 kg. Postoperatively the mean union time was 11.36 weeks, whereas the mean time for full weight bearing was 9.70 weeks. Two (4.25 %) patients had transient superficial wound infection. Four (8.51%) patients had skin irritation due to nail tips, and five (10.63%) patients had more than 1cm of limb length discrepancy. Limb malalignment >10 degrees was noted in two (4.25%). At the end of nine months, 70.21% reported excellent, 25.53% satisfactory, and 4.25% poor outcomes as per Flynn’s criteria.Conclusion: Titanium Elastic Nailing System is a minimally invasive pediatric femur fracture fixation method with relatively few associated complications and predictable favorable outcomes.